SYNERGISTIC EFFECTS OF CITRIC ACID AND PHYTASE SUPPLEMENTED CANOLA MEAL BASED DIET ON GROWTH PERFORMANCE AND NUTRIENT DIGESTIBILITY OF CYPRINUS CARPIO FINGERLINGS - M. Z. Arsalan; S. M. Hussain; A. Javid; M. Hussain; R. Manzoor; M. M. Jalees; M. M. Rehan; A. Sharif (Journal of Animal and Plant Sciences, 2023)
A 3×3 factorial arrangement was used to determine the synergistic effects of citric acid (CA) and phytase (PHY) supplemented canola meal (CM) based diet on growth performance and nutrient digestibility of Cyprinus carpio fingerlings. Canola meal was used as a main ingredient to prepare diets by replacing fishmeal at graded levels such as: 0%, 25%, 50% and 75%. These diets were further supplemented by different levels of CA (0% and 2.5%) and PHY (0 and 750 FTU kg-1) to formulate a total of 16 test diets. Completely Randomized Design (CRD) was followed to add diets to the fish groups. Chromic oxide (Cr2O3) was added as an indigestible marker. Fish were fed at the rate of 5% of their live wet weight. The findings of study revealed that the maximum weight gain% (267.81%), SGR (1.44) and the lowest value of FCR (1.32) were noted when fingerlings were fed on test diet T12 containing 50% canola meal with 750 FTUkg-1 PHY and 2.5% CA supplementation as compared to fish fed on control diet (T1) having 0% canola meal and without any concentration of CA and PHY. Similarly, optimum nutrient digestibility values such as crude protein (75.06%), crude fat (83.31%) and gross energy (66.45%) were noted when fish fed on the same diet (T12). It may be concluded that fish meal could be optimally replaced with canola meal up to 50%, when supplemented with PHY (750 FTU kg-1) and CA (2.5%).
Keywords: C. carpio; phytase; citric acid; canola meal; growth; nutrient digestibility